FT-IR studies of sickle hemoglobin interaction with phosphatidylserine. Issue 3 (2004) - Ouyang Ouyang, Hao Hao; Moore Moore, David J. David J.; Sills Sills, Richard H. Richard H.; Mendelsohn Mendelsohn, Richard Richard
Abstract : The interaction of dilauroylphosphatidylserine (DLPS) vesicles with both normal human hemoglobin (HbA) and hemoglobin from patients with sickle cell disease (HbS) has been investigated with FTIR spectroscopy. Changes in the conformational order of the phospholipid chains were directly monitored via the acyl chain CH2 symmetric stretching mode frequencies. The hemoglobin oxygenation state was simultaneously monitored via the S−H stretching contour. The current study reveals that under oxygenated conditions, DLPS shows little interaction with either HbA or HbS. In contrast, deoxyHbS interacted with DLPS by abolishing the gel−liquid crystal phase transition.